Ecstasy-induced recurrent toxic hepatitis in a young adult - DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN; ONUR, ÖZGE ECMEL (ELSEVIER, 2008)
BACKGROUND: The drug 3,4-methylenedioxymethamphetamine (MDMA), otherwise known as ecstasy, is a synthetic amphetamine that produces euphoria, increases sociability and energy, and is often used as a weekend recreational drug by young adults. CASE SUMMARY: A 23-year-old male (height, 184 cm; weight, 68 kg) presented to the emergency department of Marmara University Hospital, Istanbul, Turkey, with jaundice and nausea lasting for 6 days. The patient reported that he had been a chronic user of MDMA for 2 years. He also reported that I week before presenting, he had ingested twice (2 tablets) the usual amount (I tablet) of the drug at the same time. Blood tests were performed and hematologic findings were as follows: aspartate aminotransferase (AST), 1423 U/L (reference range, 10-37 U/L); alanine aminotransferase (ALT), 2748 U/L (10-40 U/L); alkaline phosphatase, 271 U/L (0-270 U/L); gamma-glutamyl transpeptidase, 124 U/L (7-49 U/L); total bilirubin, 13.23 mg/dL (0.2-1 mg/dL); direct bilirubin, 8.75 mg/dL (0-0.3 mg/dL); amylase, 80 U/L (0-220 U/L); prothrombin time, 21.2 sec; activated partial thromboplastin time, 37.3 sec; and international normalized ratio, 1.66. Liver enzymes and bilirubin levels were found to be extremely high (AST = 40x normal, ALT = 70x normal, and bilirubin = 13x normal). Viral, autoimmune, and metabolic causes were excluded. Serologic tests for hepatitis A, B, and C viruses, mononucleosis, cytomegalovirus, and HIV infection were all negative. A diagnosis of ecstasy-induced toxic hepatitis was made. The patient's medical history further revealed that the current incident was actually his second occurrence of jaundice and acute hepatitis associated with the ingestion of higher amounts (twice the usual amount of MDMA he ingested at the same time). Supportive therapy (IV saline and vital sign monitoring) was initiated and liver enzymes, bilirubin levels, and prothrombin times were monitored daily. All had returned to normal values in 2 weeks. CONCLUSIONS: MDMA, or the recreational drug ecstasy, might be responsible for acute hepatitis and/or acute liver failure, particularly in young people. Physicians might need to be alert to the possibility of ecstasy-induced liver damage occurring in younger patients, although the presence of other hepatotoxins and alternative diagnoses requires exclusion. The use of this drug should be investigated in young patients with severe hepatitis of unknown origin.
Keywords: 3,4-methylenedioxymethamphetamine; MDMA; ecstasy; recurrent acute hepatitis; MDMA; HEPATOTOXICITY; MANAGEMENT; CYP2D6; MISUSE; DRUGS